KESESUAIAN TIPE KEPRIBADIAN DENGAN PEKERJAAN SEBAGAI GURU DAN HUBUNGANNYA DENGAN KINERJA GURU - Ismira Ismira (Indonesian Institute for Counseling, Education and Therapy (IICET), 2016)
Personality type is one of the factors that influence the effectiveness of individuals in work. If someone gets a job based on his personality type, then people will feel happy proficiency level, effective and productive in their work. Teacher is a job that many acted by the community. Teachers have a very strategi c role in efforts to achieve goal of National Education. Problems occurred, many teachers do not have the type of personality that fit the job as a teacher. This will affect the effectiveness of teacher performance and of course will affect the quality of graduates. This study aims to describe the suitability of the type of personalit y to work as a teacher, describing the performance of teachers and describe personality types contribute to the improvement of teacher performance. Research using quantitative methods with Simple Regression Analysis Technique. Research tools using an inventory t ype of personality John L. Holand and performance questionnaire with Likert scale.